Analysis of circuit operation under ZVS and NON-ZVS conditions in phase-shift inverter for induction heating - Viriya, Pichetjamroen; Yongyuth, Naras; Miki, Ichiro; Matsuse, Kouki (My University, 2006)
This paper presents a detailed analysis of circuit operation under ZVS and NON-ZVS conditions in a full-bridge high-frequency phase-shift control series resonant MOSFET inverter with the load of induction heating. Various modes of circuit operation both under ZVS and NON-ZVS conditions are first analyzed in details. The voltage and current equations of these circuits are then obtained and used for calculation of the waveforms by MATLAB program. The calculated results can lead to the consideration of various circuit parameters that determine ZVS or NON-ZVS operating conditions. The theoretical results are also verified by experimental ones, using a prototype test set rated at 3 kW.
Keywords: Circuit operation; High-frequency; Induction heating; NON-ZVS; Phase-shift; ZVS